Pengaruh Jumlah Penduduk, Upah Minimum dan PDRB Terhadap Tingkat Pengangguran Terbuka di Provinsi Nusa Tenggara Timur - Baiq Reka Yustika; Muhammad Ghofur Wibowo; Anava Salsa Nur Savitri; Ahmad Ulil Albab Al Umar (CV. Ulil Albab Corp, 2024)
This research discusses the influence of Population, Minimum Wage, and GRDP on the Open Unemployment Rate in East Nusa Tenggara (NTT) Province. This research aims to determine the effect of Population, Minimum Wage, and GRDP on the Open Unemployment Rate in East Nusa Tenggara (NTT) Province. The data analysis method used is panel data regression analysis. Panel data analysis used model selection, classical assumption, and significance tests. The analytical tool used is Eviews 10. The results of this research are that Population and GRDP do not affect the Open Unemployment Rate in NTT Province, while the Minimum Wage has a positive and significant effect on the Open Unemployment Rate in NTT Province.